2006
DOI: 10.1182/blood.v108.11.1552.1552
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous (IV) Iron Supplementation in Patients with Chemotherapy-Induced Anemia (CIA) Receiving Darbepoetin alfa Every 3 Weeks (Q3W): Iron Parameters in a Randomized Controlled Trial.

Abstract: Background and Aim: The role of IV iron supplementation during treatment with erythropoiesis-stimulating agents (ESAs) in patients with CIA is of increasing interest as a possible means of improving response. This randomized, open-label, multicenter study was designed to evaluate the safety and efficacy of IV iron vs standard practice in CIA patients receiving darbepoetin alfa. Interim efficacy analyses showed a higher response rate for darbepoetin alfa with IV iron compared to darbepoetin alfa with standard i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…As discussed previously, the benefits of iron supplementation during ESA therapy have been well established in chemotherapy-induced anemia, even in patients with TSAT levels of 20-35% and sFerr levels of 100-900 ng/mL. [33][34][35][36][37][38][39] Furthermore, recent pharmacoeconomic analysis demonstrated significantly improved cost-effectiveness of ESA therapy when used in conjunction with intravenous iron; the addition of intravenous iron resulted in a cost saving of $1300 per 12-week treatment cycle per patient. 1 Multiple studies have indicated that intravenous iron supplementation enhances ESA therapy in patients with chemotherapy-induced anemia whose TSAT levels are <35% and sFerr levels are 100-900 ng/mL.…”
Section: Cancermentioning
confidence: 92%
See 2 more Smart Citations
“…As discussed previously, the benefits of iron supplementation during ESA therapy have been well established in chemotherapy-induced anemia, even in patients with TSAT levels of 20-35% and sFerr levels of 100-900 ng/mL. [33][34][35][36][37][38][39] Furthermore, recent pharmacoeconomic analysis demonstrated significantly improved cost-effectiveness of ESA therapy when used in conjunction with intravenous iron; the addition of intravenous iron resulted in a cost saving of $1300 per 12-week treatment cycle per patient. 1 Multiple studies have indicated that intravenous iron supplementation enhances ESA therapy in patients with chemotherapy-induced anemia whose TSAT levels are <35% and sFerr levels are 100-900 ng/mL.…”
Section: Cancermentioning
confidence: 92%
“…22,23, 25 Hepcidin interferes with enteral iron absorption and promotes iron degradation; the mechanism by which hepcidin promotes the degradation of iron is interference with both the iron release from macrophages and iron transport by ferroportin. Table 2 4,33-41 and Table 3 4, [33][34][35][36][37][38][39][40][41][42][43][44] summarize factors that need to be considered when assessing for iron deficiency and specific indicators for iron deficiency, respectively.…”
Section: Assessment Of Iron Deficiency and Intravenous Iron Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, three studies have been reported so far in abstract form only. The first was a trial of 400 cancer patients with chemotherapy‐induced anaemia treated with darbepoetin in which patients were randomised to intravenous iron (Venofer ® ) or standard care (29% of whom received oral iron) (Lerchenmueller et al , 2006; Vandebroek et al , 2006). An interim analysis suggests an improved haemoglobin response in the intravenous iron group.…”
Section: Anaemia In Patients With Cancermentioning
confidence: 99%
“…However, longer‐acting ESAs have been developed. One study 39 showed a statistically significant increment in hemoglobin levels and a decrease in transfusion requirements in patients receiving darbepoetin alfa every 3 weeks plus intravenous ferric gluconate or iron sucrose. These data were not stratified for baseline iron parameters.…”
Section: How To Administer Parenteral Ironmentioning
confidence: 99%